Investigating women’s awareness and perceptions on human papillomavirus infection and oropharyngeal cancer in Italy - Paduano, Giovanna; Vaienna, Sara; Maisto, Giuseppe; Di Giuseppe, Gabriella; Pavia, Maria (Frontiers in Public Health, 2023)
Introduction This study explored knowledge, attitudes and behaviors toward human papillomavirus (HPV) infection and oropharyngeal cancer (OPC) among women attending primary care services. Methods The cross-sectional study was conducted from September to December 2022 in adult women attending three primary care services in Italy, who were invited to complete a self-administered questionnaire. Results Overall, 34.7% of participants know that OPC is HPV-associated; knowledge was higher among women who had personal, familiar or friends’ experience of cancer, and who reported to often seek dental care, whereas it was lower in older women. The perception of risk of developing OPC was high for 26.4% of women and was higher in those who had experienced STD, who knew that early sexual debut is a risk factor for OPC, and who considered useful the role of dentists on the provision of information about OPC. Only 22.5% had received HPV vaccination, but 62% intended to receive it in the future. Moreover, 63.2% believe that HPV vaccination is very useful to prevent OPC and only 27% are concerned about health consequences of HPV vaccination. Conclusion These findings indicate that women’s awareness of the role of HPV infection in the development of OPC is not satisfactory and underline the role that dentists might have in improving their patients’ awareness on HPV related OPC.